Food Innovation: Fungi and Vegetables Potential as A Healthy and Sustainable Meat Substitute - Muliani, Debby; Nathania, Evelyn Adela; J, Jeslin; Jayanti, Yasmin Nadira; Hadrian, Edwin (Indonesian Journal of Life Sciences, 2021)
One of the factor-driven global environmental concerns and health issues is excessive meat production and consumption. The popularity of meat substitutes for the benefit of sustainability and well-being has been increasing. This review highlights the health benefits, sustainability, and sensorial properties of plant-based materials as meat substitutes. Each of the materials has its advantages and disadvantages. Mushrooms, mycoprotein, soy, TVP, and seitan have a high potential to become a healthier and more sustainable meat alternative. However, there are some challenges, such as mushrooms' wide variety, mycoprotein production cost, beany and grainy nodes of soy-based products, increased seitan production that negatively impacts the environment, and low protein content of jackfruit. Nuts, cauliflower, potato, and eggplant require significant sensory improvement to mimic meat characteristics despite their environmental advantages. Moreover, their protein content and quality are low. On the other hand, Cottonseed proteins contain toxic gossypol, and research on their sustainability and nutritional value is limited. For legumes and lentils, their processing reduces some nutritional components and their taste and texture from meat. Overall, these fungi and vegetables possess great potential as meat substitutes due to their high nutritive value, workable sensorial properties, and good sustainability compared to conventional meat despite having their challenges to become potential plant-based meat products.